Extracellular Vesicles: Decoding a New Language for Cellular Communication in Early Embryonic Development - Cruz, Lilian; Romero, Jenny A. A.; Iglesia, Rebeca P.; Lopes, Marilene H. (Frontiers in Cell and Developmental Biology, 2018)
The blastocyst inner cell mass (ICM) that gives rise to a whole embryo in vivo can be derived and cultured in vitro as embryonic stem cells (ESCs), which retain full developmental potential. ICM cells receive, from diverse sources, complex molecular and spatiotemporal signals that orchestrate the finely-tuned processes associated with embryogenesis. Those instructions come, continuously, from themselves and from surrounding cells, such as those present in the trophectoderm and primitive endoderm (PrE). A key component of the ICM niche are the extracellular vesicles (EVs), produced by distinct cell types, that carry and transfer key molecules that regulate target cells and modulate cell renewal or cell fate. A growing number of studies have demonstrated the extracellular circulation of morphogens, a group of classical regulators of embryo development, are carried by EVs. miRNAs are also an important cargo of the EVs that have been implicated in tissue morphogenesis and have gained special attention due to their ability to regulate protein expression through post-transcriptional modulation, thereby influencing cell phenotype. This review explores the emerging evidence supporting the role of EVs as an additional mode of intercellular communication in early embryonic and ESCs differentiation.